6(6-3)-3=

Simple and best practice solution for 6(6-3)-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(6-3)-3= equation:


Simplifying
6(6 + -3) + -3 = 0

Combine like terms: 6 + -3 = 3
6(3) + -3 = 0

Multiply 6 * 3
18 + -3 = 0

Combine like terms: 18 + -3 = 15
15 = 0

Solving
15 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -14m-11=85 | | 2/3m-2=10 | | 2x=x-2+54 | | 975/195=p/1 | | (2y+8x)= | | -8(1+4x)-168= | | 48/96=g/6 | | 8+4=-4 | | 17-19=-2x | | (x-2)(x+3+3i)(x+3-3i)=0 | | 2y^3-10y^2-72y=0 | | 531/v=675/750 | | 9x-20=26x+30 | | 4y-18+y+14= | | 12Y=99 | | 539.4=x-231.1 | | 2q+24=26q | | 5a^2+19a=-30 | | 473/u=731/578 | | 9x^2+8=9 | | 121x^2-196=0 | | 2.5+x=-4.5 | | 2x^3-90x^2-392x=0 | | 17/b=85/50 | | 1.4x+3=9 | | 3x^2=-4+2x | | 4p-15=3p+6 | | 6y=-12x+30 | | 20/8=50/d | | u+45=46u | | 4y-6=-30 | | 6x+18x-2=6(4x+9) |

Equations solver categories